2014
DOI: 10.1590/s0100-736x2014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Produção e composição do leite e escore corporal de cabras lactantes submetidas à suplementação mineral comercial e seletiva

Abstract: A comparação da produção e composição do leite, do escore corporal e dos custos com a suplementação mineral comercial e seletiva foi feita utilizando-se dois grupos de 16 cabras lactantes por 164 dias. Não houve diferenças significativas na produção de leite dos animais que ingeriram os dois tipos de suplementos minerais. Não houve efeito do tipo de suplementação mineral em relação a composição do leite em gordura, proteína e lactose bem como na contagem de células somáticas (CCS). O consumo médio diário do su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Six dairy goats and four kids were necropsied. MALAFAIA et al (2014) studying milk production and composition and body score of goats lactating women submitted to commercial mineral supplementation and selective and concluded that selective mineral supplementation, proposed based on the clinical-nutritional examination of lactating goats, results in the maintenance of milk production and composition and score body; it is an efficient prophylactic measure and; reduces the cost of mineral supplementation flock.…”
Section: Discussionmentioning
confidence: 99%
“…Six dairy goats and four kids were necropsied. MALAFAIA et al (2014) studying milk production and composition and body score of goats lactating women submitted to commercial mineral supplementation and selective and concluded that selective mineral supplementation, proposed based on the clinical-nutritional examination of lactating goats, results in the maintenance of milk production and composition and score body; it is an efficient prophylactic measure and; reduces the cost of mineral supplementation flock.…”
Section: Discussionmentioning
confidence: 99%